Research bubbles - Hans Gersbach; Evgenij Komarov (ETH Zurich, CER-ETH - Center of Economic Research, 2020)
We develop a model to rationalize and examine so-called "research bubbles", i.e. research activities based on overoptimistic beliefs about the impact of this research on the economy. Research bubbles occur when researchers selfselect into research activities and the government aggregates the assessment of active researchers on the way advances in research may spur innovation and growth. In an overlapping generations framework, we study the occurrence of research bubbles and show that they tend to be welfare-improving. Particular forms can even implement the socially optimal solution. However, research bubbles can collapse, and we discuss institutional devices and the role of debt financing that ensure the sustainability of such bubbles. Finally, we demonstrate that research bubbles emerge in various extensions of our baseline model.
Keywords: E02; E71; O32; O41; 330; Endogenous Growth; Basic Research and Macro-Based Behavioral Economics